Checklist of oribatid mites (Acari, Oribatida) of the Russian Far East and Northeast of China - Ryabinin, Nikolay A.; Liu, Dong; Gao, Meixiang; Wu, Dong-Hui (Zootaxa, 2018)
The present paper reviews the taxonomic studies of the mite suborder Oribatida in the Russian Far East South and Chinese North-East Territories. At present, 746 species of oribatid mites are registered in China, including 175 species in the soils of Northeast China. In the Russian Far East, there were 605 species of oribatids, including 344 species in the south of the Far East. The fauna of the oribatid mites of the Northeast of China and the south of the Russian Far East has 446 species and subspecies representing 190 genera and 80 families. 72 species of oribatid are common for both territories. The modern fauna of the oribatid mites of the Northeast of China and the south of the Far East was formed as a result of prolonged interaction between the boreal and palaearchaearctic faunas. The oribatid fauna of this region is distinguished by the presence of a large number of endemics, some of which are relics of the late Tertiary time and which can be considered as autochthonous. The checklist includes data from more than 100 locations of this enormous region. In addition, a short climatic and historical review of oribatid mites study is presented.